Conservative Approach for Traumatic Anterior Crown-Root Fractured Teeth by Orthodontic Extrusion using Customized Mini-Tube Appliance: A Clinical Review - Sehun Lim; Youngmin Kwon (Hindawi Limited, 2023)
A complicated crown-root fracture is a fracture involving enamel, dentin, cementum, and pulp. Because crown fracture generally extends below the gingival margin, several options may be indicated to expose the margins before permanent restoration. Among them, orthodontic extrusion is the most non-invasive treatment option. In this case report, a case of traumatic crown-root fracture of the maxillary incisor was managed by root canal treatment with fiber-reinforced ceramic post-placement followed by orthodontic extrusion using a customized mini-tube appliance technique. Then, the porcelain fused zirconia crown was restored. Traumatized orthodontic extruded teeth have shown a reliable prognosis without inflammatory signs nor complications after a 15-month follow-up.